RELATIONSHIP ON THE LEVEL OF PLEASURE WORKING IN SCHOOL WITH THE PROFESSIONAL LEVEL OF TEACHERS TEACHING READING LITERATION - Safari .; Ari Sumitro; Masduki Ahmad (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
The main objective of this study is to answer the following questions. Is there a relationship between the level of pleasure of working in school and the professional level of teachers teaching reading literacy based on PISA 2018. The research method used is quantitative methods. The data in this study uses PISA 2018 data that has been released to the public and has been permitted to be used for research development purposes. The population of this study were teachers teaching 15 year old students who were studying in 2018, while the sample was teachers teaching 15 year old students who took PISA tests in 80 countries. The reason for selecting the sample is that teachers teach students who are taking the 2018 PISA test. The data in this study is in the form of a questionnaire that was answered by teachers in 80 countries, namely 89040 teachers from 80 countries. Based on the results of simple regression analysis, the results show that there is a relationship between the level of pleasure of working in school and the professional level of teachers teaching reading literacy based on PISA 2018 (P <0.000). The conclusion is that statistically there is a relationship between the level of pleasure of working in school and the professional level of teachers teaching reading literacy based on the 2018 PISA. Most of the respondents enjoy working in schools and professionals in teaching reading literacy.